Urban Chikungunya in the Middle East and North Africa: A systematic review. - John M Humphrey; Natalie B Cleton; Chantal B E M Reusken; Marshall J Glesby; Marion P G Koopmans; Laith J Abu-Raddad (PLoS Neglected Tropical Diseases)
Background The epidemiology of Chikungunya virus (CHIKV) in the Middle East and North Africa (MENA) is not well characterized despite increasing recognition of its expanding infection and disease burden in recent years. Methodology / principal findings Following Cochrane Collaboration guidelines and reporting our findings following PRISMA guidelines, we systematically reviewed records describing the human prevalence and incidence, CHIKV prevalence/infection rates in vectors, outbreaks, and reported cases for CHIKV across the MENA region. We identified 29 human seroprevalence measures, one human incidence study, one study reporting CHIKV infection rates in Aedes, and nine outbreaks and case reports/series reported in the MENA from 1970-2015. Overall, anti-CHIKV antibody or reports of autochthonous transmission were identified from 10 of 23 countries in the MENA region (Djibouti, Egypt, Iraq, Iran, Kuwait, Pakistan, Saudi Arabia, Somalia, Sudan, and Yemen), with seroprevalence measures among general populations (median 1.0%, range 0-43%) and acute febrile illness populations (median 9.8%, range 0-30%). Sudan reported the highest number of studies (n = 11) and the highest seroprevalence among general populations (median 12%, range 0-43%) and undifferentiated acute febrile illness populations (median 18%, range 10-23%). CHIKV outbreaks were reported from Djibouti, Pakistan, Sudan, and Yemen. Conclusions / significance Seroprevalence studies and outbreak reports suggest endemic transmission of urban cycle CHIKV in at least the Red Sea region and Pakistan. However, indications of seroprevalence despite a low quantity of CHIKV epidemiologic research from the region suggests that CHIKV transmission is currently underrecognized.